Pengembangan Multimedia Interaktif Berbasis Website Pada Materi Peluang - Rahman Patingki; Sarson W. Pomalato; Novianita Achmad (Transbahasa, 2025)
This research aims to produce interactive multimedia on opportunity material for class VIII Even Semester Junior High Schools. This research uses the Research and Development (R&D) research methodology. This development research follows the four-D development model. The Thiagarajan, Semmel and Semmel models consist of four stages, namely Define, Design, Develop and Disseminate. The validation results obtained from 3 media experts and 3 material experts were 84.03% and 89% with the criteria